Sheet Metal 2025 - Meschut, Gerson; Bobbert, Mathias; Duflou, J. R.; Fratini, Livan; Hagenah, Hinnerk; Martins, Paulo A.F.; Merklein, Marion; Micari, Fabrizio (Materials research Forum LLC, 2025)
The 21st edition of the SheMet Conference again summarizes ongoing research in the field of sheet metal processing. It is also bridging the gab to industrial application by contributions more oriented to realization. The focus is in the field of forming, simulation, incremental forming, machine learning, characterization, welding and additive manufacturing, polymers and composites, sustainability and joining. The book is holding the papers presenting the key findings and aspects of the given presentations.<br